A CNTs cooperated Ni and PANI composite solar evaporator and a preparation method thereof
Patent Information
- Application Number
- CN202611126694.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
但现有研究缺少碳纳米管、金属镍、聚苯胺三者逐级协同改性的完整方案,改性工序先后顺序对材料微观结构、蒸发性能的影响规律尚不清晰,无法充分发挥三类材料协同增效作用
[0025]与现有技术相比,本发明通过碳纳米管在基底表面构筑连续三维多孔网络,依靠多重光散射强化光子捕获能力,表层中间金属颗粒层与导电聚合物层形成光谱互补的吸光结构,三者协同拓宽光能吸收范围,充分利用全波段太阳能。底层碳纳米管网络依靠管间声子散射形成隔热屏障,阻挡热量向水体扩散,上层吸光组分吸收光能后将热量限定在气液蒸发界面,降低无效热损耗,提升蒸发能效。按照先负载碳纳米管、再沉积中间金属颗粒层、最后聚合导电聚合物层的顺序改性,碳纳米管网络提供高比表面积载体,中间金属颗粒层提升表面粗糙度以提供更多附着位点,保障导电聚合物均匀生长,同步集成光能捕获、水分输送、热量管控多重功能。多孔亲水输水层的三维多孔毛细网络结构可持续疏导盐分,避免盐晶堆积在多级改性光热层表面,长时间处理含盐水体仍能维持稳定蒸发性能。
Smart Images

Figure CN122916265A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photothermal functional composite materials technology, specifically to a composite solar evaporator of CNTs synergistic with Ni and PANI and its preparation method. Background Technology
[0002] Freshwater scarcity is a pressing global problem, and seawater desalination is an effective means of supplementing freshwater resources. Currently, most mainstream seawater desalination processes rely on electricity and high-temperature heat, resulting in high energy consumption and operating costs, making them difficult to implement in remote areas without electricity. Solar-powered interfacial evaporation technology, which converts solar energy into interfacial heat energy using photothermal materials, significantly reduces overall heat loss in the water body, making it a preferred low-energy seawater desalination technology.
[0003] Currently, carbon fiber paper is the commonly used photothermal substrate. This substrate has high mechanical strength and excellent electrical conductivity. However, the surface of raw carbon fiber paper is smooth and lacks active functional groups, resulting in limited absorption capacity of sunlight and low photothermal conversion efficiency. Existing modification methods for carbon fiber paper are mostly single modifications, such as depositing metal particles or polymerizing conductive polymers. These methods have drawbacks such as narrow solar absorption bands, few surface active sites, and uneven distribution of modified materials. A single modified layer cannot simultaneously achieve the three core functions of broad-spectrum light harvesting, local heat control, and continuous water supply, making it difficult to improve the overall evaporation performance of the evaporator.
[0004] Carbon nanotubes, nickel, and polyaniline are all high-performance photothermal materials. Carbon nanotubes can construct porous thermal insulation networks to confine interfacial heat, nickel can improve substrate roughness, and polyaniline has the advantage of broad-spectrum light absorption. However, current research lacks a complete scheme for the stepwise synergistic modification of carbon nanotubes, nickel, and polyaniline. The influence of the order of modification processes on the microstructure and evaporation performance of the materials is still unclear, making it impossible to fully realize the synergistic effect of the three materials.
[0005] At the same time, most solar evaporators on the market only use a single layer of photothermal material floating on the water surface and lack a dedicated high-efficiency water conveyance structure. When evaporating high-salt seawater for a long time, salt is very likely to crystallize on the surface of the photothermal layer, causing the equipment performance to continuously degrade. Summary of the Invention
[0006] The purpose of this invention is to provide a composite solar evaporator based on CNTs synergistically combined with Ni and PANI, and its preparation method. This invention constructs a multi-level synergistic and multi-level modified photothermal layer by sequentially introducing carbon nanotubes, an intermediate metal particle layer, and a conductive polymer layer onto the surface of carbon fiber paper. This layer is then combined with a porous hydrophilic water-transporting layer to form a three-dimensional composite evaporator with efficient water transport function. This achieves synergistic optimization of broad-spectrum efficient light absorption, localized heat interface, and continuous water supply, thereby improving the performance of solar-driven seawater desalination.
[0007] The technical solution provided by this invention is as follows: A composite solar evaporator of CNTs synergistic with Ni and PANI, comprising a multi-level modified photothermal layer and a porous hydrophilic water-transporting layer, wherein the multi-level modified photothermal layer comprises a substrate, the surface of which is sequentially coated from the inside out with a three-dimensional porous network layer of carbon nanotubes, an intermediate metal particle layer and a conductive polymer layer; the porous hydrophilic water-transporting layer is bonded to the bottom surface of the multi-level modified photothermal layer, and the porous hydrophilic water-transporting layer has a three-dimensional porous capillary network structure for continuous water supply and resistance to salt crystallization.
[0008] The above-mentioned method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI involves the following steps for constructing the multi-level modified photothermal layer: first, constructing a three-dimensional porous carbon nanotube network layer on the substrate surface; then, constructing an intermediate metal particle layer on the surface of the three-dimensional porous carbon nanotube network layer; and finally, constructing a surface conductive polymer layer on the surface of the intermediate metal particle layer to obtain the multi-level modified photothermal layer. A porous hydrophilic water-conducting layer is then composited onto the bottom surface of the multi-level modified photothermal layer to obtain the multi-level modified composite solar evaporator.
[0009] In the aforementioned method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI, a three-dimensional porous network layer of carbon nanotubes is first constructed on the substrate surface, including:
[0010] The substrate is immersed in a carbon nanotube dispersion for impregnation treatment, so that the carbon nanotubes are loaded on the surface and gaps of the substrate and form a three-dimensional porous network structure, thus obtaining the carbon nanotube three-dimensional porous network layer.
[0011] In the aforementioned method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI, the carbon nanotube dispersion is prepared by dispersing carboxylated multi-walled carbon nanotubes and a carbon nanotube dispersant in deionized water at a mass ratio of 0.8–1.2:1; the diameter of the carboxylated multi-walled carbon nanotubes is 10–30 μm; the mass fraction of the carbon nanotube dispersion is 0.2 wt%–1 wt%; the impregnation treatment is ultrasonic impregnation treatment, the treatment time is 25–35 min, and the impregnation treatment further includes a step of washing and drying at 60°C for 1–3 h.
[0012] In the aforementioned method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI, the step of constructing an intermediate metal particle layer on the surface of the three-dimensional porous network layer of carbon nanotubes includes:
[0013] Metal particles are loaded onto the surface of the three-dimensional porous network layer of carbon nanotubes through a deposition process to increase the surface micro-roughness and provide attachment sites for the surface conductive polymer layer, thereby obtaining the intermediate metal particle layer.
[0014] In the aforementioned method for preparing a composite solar evaporator of CNTs in conjunction with Ni and PANI, the metal particles are nickel particles;
[0015] The deposition process is an electrochemical deposition process, which includes: using the substrate loaded with the three-dimensional porous network layer of carbon nanotubes as the cathode and a pure nickel sheet as the anode, performing electrochemical deposition in a nickel sulfate electrolyte at a constant current of 0.8 to 1.2 A for 4 to 6 minutes;
[0016] The electrochemical deposition process also includes a cleaning step followed by drying at 60°C for 1–3 hours.
[0017] In the aforementioned method for preparing a composite solar evaporator of CNTs in conjunction with Ni and PANI, the final construction of a conductive polymer layer on the surface of the intermediate metal particle layer includes:
[0018] A conductive polymer layer is formed on the surface of the intermediate metal particle layer through a polymerization process to obtain the conductive polymer layer.
[0019] In the aforementioned method for preparing a composite solar evaporator of CNTs in conjunction with Ni and PANI, the conductive polymer layer is a polyaniline layer;
[0020] The polymerization process is an in-situ oxidative polymerization process, which includes: immersing the substrate loaded with the intermediate metal particle layer in an aniline solution with a concentration of 0.25-0.35 mol / L, then adding an ammonium persulfate solution with a concentration of 0.25-0.35 mol / L, and carrying out the oxidative polymerization reaction at a low temperature of 0-5°C for 3-5 hours;
[0021] The oxidative polymerization reaction is followed by washing and drying at 60°C for 1–3 hours.
[0022] In the aforementioned method for preparing a composite solar evaporator using CNTs in conjunction with Ni and PANI, the step of assembling a porous hydrophilic water-conducting layer onto the bottom surface of the multi-level modified photothermal layer includes:
[0023] A cellulose aerogel is bonded to the bottom surface of the multi-stage modified photothermal layer using an adhesive to form the porous hydrophilic water-conducting layer.
[0024] In the aforementioned method for preparing a composite solar evaporator using CNTs in conjunction with Ni and PANI, the cellulose aerogel is prepared by freezing and freeze-drying a mixed solution of polyvinyl alcohol and nanocellulose in liquid nitrogen. The freeze-drying temperature is -55 to -45°C and the vacuum degree is 0.05 to 0.07 MPa. The binder is a mixed solution of polyvinyl alcohol and nanocellulose. After bonding, the process further includes a step of curing by drying at 60°C for 1 to 3 hours.
[0025] Compared with existing technologies, this invention constructs a continuous three-dimensional porous network on the substrate surface using carbon nanotubes. This network enhances photon capture through multiple light scattering, while the surface layer, intermediate metal particles, and conductive polymer layer form a spectrally complementary light-absorbing structure. These three elements synergistically broaden the light absorption range, fully utilizing solar energy across the entire wavelength range. The bottom carbon nanotube network forms a thermal barrier through inter-tube phonon scattering, preventing heat diffusion into the water. The upper light-absorbing components absorb light energy and confine the heat to the gas-liquid evaporation interface, reducing ineffective heat loss and improving evaporation efficiency. By modifying the substrate sequentially—first loading carbon nanotubes, then depositing the intermediate metal particle layer, and finally polymerizing the conductive polymer layer—the carbon nanotube network provides a high specific surface area carrier, the intermediate metal particle layer increases surface roughness to provide more attachment sites, ensuring uniform growth of the conductive polymer, and simultaneously integrating multiple functions such as light capture, water transport, and heat management. The three-dimensional porous capillary network structure of the porous hydrophilic water-transporting layer continuously guides salt, preventing salt crystal accumulation on the surface of the multi-level modified photothermal layer, maintaining stable evaporation performance even after long-term treatment of saline bodies. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the preparation process of the present invention. Detailed Implementation
[0027] The present invention will be further described below with reference to the embodiments and accompanying drawings, but this should not be construed as limiting the present invention.
[0028] Example 1: A composite solar evaporator of CNTs in synergy with Ni and PANI and its preparation method, as shown in the attached figure. Figure 1As shown, a cellulose aerogel with a three-dimensional porous network structure was prepared by mixing polyvinyl alcohol (PVA) and cellulose nanofiber (CNF) in a 1:1 mass ratio and then freeze-drying (-50℃, vacuum 0.06MPa) using liquid nitrogen. This aerogel served as a porous hydrophilic water-transporting layer for subsequent composite assembly. 0.5g of carbon nanotube dispersant was added to 49g of deionized water and ultrasonically stirred until dissolved. 0.5g of carboxylated multi-walled carbon nanotubes were then added and thoroughly dispersed using an ultrasonic cell disruptor to prepare a 1wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 1wt% carbon nanotube dispersion. The paper was ultrasonically impregnated for 30min, then rinsed with deionized water and dried at 60℃ for 2h to obtain a carbon nanotube-loaded substrate (CP@CNT). A nickel sulfate electrolyte was prepared. A substrate loaded with carbon nanotubes was used as the cathode and a pure nickel sheet was used as the anode. The substrate was placed in the nickel sulfate electrolyte and electrochemical deposition was performed at a constant current of 1A for 5 minutes using an adjustable DC regulated power supply (MS305D type). After deposition, the sample was taken out, thoroughly washed with deionized water, and dried at 60℃ for 2 hours to obtain an intermediate material (CP@CNT-Ni) with an intermediate nickel metal particle layer. 20 mL each of 0.3 mol / L aniline solution and 0.3 mol / L ammonium persulfate solution were prepared. The intermediate material with the intermediate nickel metal particle layer was immersed in the aniline solution and sonicated for 5 min for pre-impregnation. Then, the ammonium persulfate solution was slowly added, and in-situ oxidative polymerization was carried out at a low temperature of 0-5℃ for 4 h. The material was washed with ethanol and deionized water in sequence and dried at 60℃ for 2 h to prepare a multi-stage modified photothermal layer (CP@CNT-Ni-PANI). An appropriate amount of polyvinyl alcohol and nanocellulose mixed solution was uniformly coated on the bottom surface of the multi-stage modified photothermal layer. Cellulose aerogel was then bonded to it, ensuring full contact between the two. The assembly was placed in a drying oven at 60℃ for 2 h to prepare a multi-stage modified composite solar evaporator (CP@CNT-Ni-PANI-CA).
[0029] Example 2: A composite solar evaporator of CNTs synergistic with Ni and PANI and its preparation method. A mixed solution of polyvinyl alcohol and nanocellulose was prepared at a 1:1 mass ratio. A cellulose aerogel with a three-dimensional porous network structure was prepared by liquid nitrogen freezing and freeze-drying (-50℃, vacuum 0.06MPa), serving as a porous hydrophilic water-transporting layer for subsequent composite assembly. 0.1g of carbon nanotube dispersant was added to 49.8g of deionized water and ultrasonically stirred until dissolved. 0.1g of carboxylated multi-walled carbon nanotubes were added and thoroughly dispersed using an ultrasonic cell disruptor to prepare a 0.2wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 0.2wt% carbon nanotube dispersion. The paper was ultrasonically impregnated for 30min, then removed, washed with deionized water, and dried at 60℃ for 2h to obtain a substrate loaded with carbon nanotubes. A nickel sulfate electrolyte was prepared. A substrate loaded with carbon nanotubes was used as the cathode and a pure nickel sheet was used as the anode. The substrate was placed in the nickel sulfate electrolyte and electrochemical deposition was performed at a constant current of 0.8A for 4 minutes using an adjustable DC regulated power supply. After deposition, the sample was taken out, thoroughly washed with deionized water, and dried at 60℃ for 2 hours to obtain an intermediate material with an intermediate nickel metal particle layer. 20 mL each of 0.25 mol / L aniline solution and 0.25 mol / L ammonium persulfate solution were prepared. The intermediate material with the intermediate nickel metal particle layer was immersed in the aniline solution and sonicated for 5 min for pre-impregnation. Then, the ammonium persulfate solution was slowly added, and in-situ oxidative polymerization was carried out at a low temperature of 0-5℃ for 3 h. The material was washed with ethanol and deionized water in sequence and dried at 60℃ for 2 h to prepare a multi-stage modified photothermal layer. An appropriate amount of polyvinyl alcohol and nanocellulose mixed solution was uniformly coated on the bottom surface of the multi-stage modified photothermal layer. Cellulose aerogel was then bonded to it, ensuring full contact between the two. The assembly was placed in a drying oven at 60℃ for 2 h to prepare a multi-stage modified composite solar evaporator.
[0030] Example 3: A composite solar evaporator of CNTs synergistic with Ni and PANI and its preparation method. A mixed solution of polyvinyl alcohol and nanocellulose was prepared in a 1:1 mass ratio. A cellulose aerogel with a three-dimensional porous network structure was prepared by liquid nitrogen freezing and freeze-drying (-50℃, vacuum degree 0.06MPa), which served as a porous hydrophilic water-transporting layer for subsequent composite assembly. 0.3g of carbon nanotube dispersant was added to 49.4g of deionized water and ultrasonically stirred until dissolved. 0.3g of carboxylated multi-walled carbon nanotubes were added to the solution and dispersed thoroughly using an ultrasonic cell disruptor to prepare a 0.6wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 0.6wt% carbon nanotube dispersion. After ultrasonic impregnation for 30min, the paper was removed, washed with deionized water, and dried at 60℃ for 2h to obtain a substrate loaded with carbon nanotubes. A nickel sulfate electrolyte was prepared. A substrate loaded with carbon nanotubes was used as the cathode and a pure nickel sheet was used as the anode. The substrate was placed in the nickel sulfate electrolyte and electrochemical deposition was performed under a constant current of 1.2A for 6 minutes using an adjustable DC regulated power supply. After deposition, the sample was taken out, thoroughly washed with deionized water, and dried at 60°C for 2 hours to obtain an intermediate material with an intermediate nickel metal particle layer. 20 mL each of 0.35 mol / L aniline solution and 0.35 mol / L ammonium persulfate solution were prepared. The intermediate material with the intermediate nickel metal particle layer was immersed in the aniline solution and sonicated for 5 min for pre-impregnation. Then, the ammonium persulfate solution was slowly added, and in-situ oxidative polymerization was carried out at a low temperature of 0-5℃ for 5 h. The material was washed with ethanol and deionized water in sequence and dried at 60℃ for 2 h to prepare a multi-stage modified photothermal layer. An appropriate amount of polyvinyl alcohol and nanocellulose mixed solution was uniformly coated on the bottom surface of the multi-stage modified photothermal layer. Cellulose aerogel was then bonded to it, ensuring full contact between the two. The assembly was placed in a drying oven at 60℃ for 2 h to prepare a multi-stage modified composite solar evaporator.
[0031] Comparative Example 1: 0.1 g of carbon nanotube dispersant was added to 49.8 g of deionized water and ultrasonically stirred in an ultrasonic cleaner until completely dissolved. 0.1 g of carboxylated multi-walled carbon nanotubes were added to the above solution and ultrasonically dispersed using an ultrasonic cell disruptor to prepare a carbon nanotube dispersion with a mass fraction of 0.2 wt%. 3 cm × 3 cm carbon fiber paper was completely immersed in the 0.2 wt% carbon nanotube dispersion and ultrasonically impregnated in an ultrasonic cleaner for 30 min. After removal, it was washed with deionized water and dried in a 60℃ drying oven for 2 h to obtain a substrate loaded with carbon nanotubes.
[0032] Comparative Example 2: 0.5g of carbon nanotube dispersant was added to 49g of deionized water and ultrasonically stirred until dissolved. 0.5g of carboxylated multi-walled carbon nanotubes were added to the solution and dispersed thoroughly using an ultrasonic cell disruptor to prepare a 1wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 1wt% carbon nanotube dispersion. The paper was ultrasonically impregnated for 30min, then removed, washed with deionized water, and dried at 60℃ for 2h to obtain a substrate loaded with carbon nanotubes.
[0033] Comparative Example 3: 0.5g of carbon nanotube dispersant was added to 49g of deionized water and ultrasonically stirred until dissolved. 0.5g of carboxylated multi-walled carbon nanotubes were added and dispersed thoroughly using an ultrasonic cell disruptor to prepare a 1wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 1wt% carbon nanotube dispersion. The paper was ultrasonically impregnated for 30min, then washed with deionized water and dried at 60℃ for 2h to obtain a carbon nanotube-loaded substrate. 20mL each of a 0.3mol / L aniline solution and a 0.3mol / L ammonium persulfate solution were prepared. The carbon nanotube-loaded substrate was immersed in the aniline solution and ultrasonically treated for 5min to allow the aniline monomer to penetrate the micropores of the material. Then, ammonium persulfate solution was slowly added, and the substrate was placed in a refrigerator at 0–5℃ for in-situ oxidative polymerization for 4h. After polymerization, the substrate was washed sequentially with anhydrous ethanol and deionized water and dried at 60℃ for 2h to obtain a carbon nanotube and polyaniline composite substrate.
[0034] Comparative Example 4: 0.5g of carbon nanotube dispersant was added to 49g of deionized water and ultrasonically stirred until dissolved. 0.5g of carboxylated multi-walled carbon nanotubes were added to the solution and dispersed thoroughly using an ultrasonic cell disruptor to prepare a 1wt% carbon nanotube dispersion. Carbon fiber paper was cut into 3cm×3cm pieces and completely immersed in the 1wt% carbon nanotube dispersion. After ultrasonic impregnation for 30min, the paper was removed, washed with deionized water, and dried at 60℃ for 2h to obtain a substrate loaded with carbon nanotubes. A nickel sulfate electrolyte was prepared, with the carbon nanotube-loaded substrate as the cathode and a pure nickel sheet as the anode. The substrate was placed in the electrolyte, and electrochemical deposition was performed for 5min under a constant current of 1A using an adjustable DC regulated power supply. After deposition, the sample was removed, thoroughly washed with deionized water, and dried at 60°C for 2 hours to obtain an intermediate material with a layer of intermediate nickel metal particles. 20 mL each of 0.3 mol / L aniline solution and 0.3 mol / L ammonium persulfate solution were prepared. The intermediate material with the intermediate nickel metal particle layer was immersed in the aniline solution and pre-impregnated by sonication for 5 minutes. Then, ammonium persulfate solution was slowly added, and in-situ polymerization was carried out at a low temperature of 0–5°C for 4 hours. The sample was washed sequentially with ethanol and deionized water and dried at 60°C for 2 hours to obtain a multi-level modified photothermal layer.
[0035] In Examples 1-3 of this invention, Example 1 exhibits the best evaporation efficiency and environmental adaptability. The photothermal materials prepared in Example 1 are compared with those prepared in Comparative Examples 1-4. In Comparative Example 1, only a small amount of carbon nanotubes are attached to the carbon fiber surface, resulting in low coverage. Most of the carbon fiber remains exposed. The water contact angle test results show that a 10 μL water droplet penetrates rapidly after contacting the sample surface, and the contact angle drops to 0° within 0.08 s, exhibiting superhydrophilic properties. This indicates that the carboxyl functional groups and porous network structure on the surface of the carbon nanotubes effectively enhance the hydrophilicity of the material. Under one standard sunlight irradiation condition, the steady-state temperature of the photothermal conversion in Comparative Example 1 is higher than that of the unmodified substrate. Compared to Control Example 1, the amount of carbon nanotubes attached to the carbon fiber surface in Comparative Example 2 was significantly increased. The carbon nanotubes densely coated the carbon fiber surface in an interlaced manner, constructing a continuous three-dimensional porous network structure, resulting in a significantly increased specific surface area. Water contact angle testing showed that the contact angle dropped to 0° within 0.08 s after droplet contact with the sample, demonstrating superior superhydrophilicity compared to Control Example 1 with its low concentration of carbon nanotubes. Under standard sunlight irradiation conditions, the average surface temperature of Comparative Example 2 was higher than that of Control Example 1 within 60 s before the light was turned off, indicating better photothermal conversion performance, consistent with the multiple light scattering enhancement mechanism of its continuous three-dimensional carbon nanotube network. SEM morphology of Comparative Example 3 showed that in-situ polymerized polyaniline particles were loaded onto the carbon nanotube coating layer, but the particle distribution uniformity was generally poor, with some areas showing agglomeration of in-situ polymerized polyaniline. Water contact angle testing showed that the material possessed hydrophilic properties, with the contact angle dropping to 0° at 0.20 s. SEM analysis of Comparative Example 4 showed that the surface particles were uniformly and densely distributed on the three-dimensional porous network of carbon nanotubes, exhibiting better uniformity than Comparative Example 3. XPS characterization confirmed that the material surface contained C-C and CO bonds, as well as amine nitrogen (-NH-, 399.5 eV), imine nitrogen (=N-), and polaron nitrogen (=N-). The presence of polaron nitrogen indicates that the in-situ polymerized polyaniline is in a highly conductive doped state. UV-Vis-NIR diffuse reflectance spectroscopy results show that the average light absorption rate of Control Example 4 reached 97.5% across the entire 280–2500 nm wavelength range, an increase of 13.6% compared to the unmodified substrate (83.9%). Compared to Control Example 3 (97.2%), it achieved further light absorption improvement in the near-infrared band (700–2500 nm). Photothermal conversion tests show that under standard sunlight conditions, the average surface temperature of Control Example 4 was 73.3℃ within 60 seconds before the lights were turned off, verifying the synergistic effect mechanism of the thermal resistance of the carbon nanotube network bottom layer and the synergistic light absorption of the upper intermediate metal particle layer and conductive polymer layer. In the indoor evaporation performance test of Example 1, under constant temperature and humidity conditions, with a standard solar intensity (AM1.5G), When the multi-stage modified composite solar evaporator is irradiated in a pure water system, the evaporation rate of Example 1 gradually reaches a steady state after 1 hour and reaches its peak at 2 hours. The corresponding steam evaporation efficiency is 98.3%, which is 32.5% higher than CP-CA and 7.9% higher than CP@Ni-PANI-CA; in simulated seawater with 3.5 wt% NaCl, the peak evaporation rate after 2 hours is... Compared to pure water, the performance degradation was reduced by 11.8%, indicating a low performance decay rate. In Example 1, an 8-hour continuous evaporation test was conducted in simulated seawater containing 3.5 wt% NaCl, and the cumulative evaporation within 8 hours reached [amount missing]. The evaporation rate peaks at 2 hours. It fluctuated slightly afterward, and remained at [a certain level] until the end of the 8-hour test. The concentration decreased by only 6.7% from the peak value. After the test, the material surface remained moist, and no salt crystallization was observed. This indicates that the capillary water transport mechanism of the cellulose aerogel effectively prevents the accumulation of salt on the surface of the multi-stage modified photothermal layer, exhibiting excellent long-term resistance to salt crystallization. Example 1 was placed in an outdoor natural sunlight environment, and a full-day evaporation test was conducted from 8:00 to 17:00. The cumulative water evaporation during the test period was... The evaporation rate increased continuously with rising light intensity and ambient temperature between 8:00 and 14:00, reaching its peak at 14:00. Compared to CP@Ni-PANI-CA, it improved by 9.1%. After 14:00, as the light intensity decreased and the humidity increased, the evaporation rate decreased accordingly. The overall trend of change was highly consistent with the environmental parameters, demonstrating good environmental adaptability.
[0036] In summary, the multi-stage modified composite solar evaporator of this invention possesses several technical advantages. Firstly, it achieves broad-spectrum, high-efficiency light absorption. Carbon nanotubes form a continuous three-dimensional porous network on the surface of a carbon fiber substrate, enhancing photon capture capability through multiple light scattering. The outer layer of nickel particles and polyaniline form a complementary light-absorbing system in the visible to near-infrared range. These three elements synergistically broaden the solar light absorption range, achieving an average light absorption rate of 97.5% across the entire 280–2500 nm wavelength band, a 13.6% improvement compared to the original carbon fiber paper (83.9%), fully utilizing solar energy across the entire wavelength band. Secondly, it achieves multi-stage synergistic photothermal efficiency enhancement and localized heat interface control. The bottom carbon nanotube network forms a thermal barrier through inter-tube phonon scattering, effectively preventing heat diffusion into the water. The upper light-absorbing components absorb light energy and concentrate the heat energy at the gas-liquid evaporation interface, reducing ineffective heat loss and improving steam production efficiency. This invention specifies a modification sequence of first loading carbon nanotubes, then electrodepositing metallic nickel, and finally polymerizing polyaniline. The carbon nanotube network provides a high specific surface area carrier, while the nickel particle layer increases surface roughness and provides sufficient adhesion sites, ensuring uniform growth of polyaniline. It simultaneously integrates multiple functions such as light energy capture, capillary water transport, and heat management. The material exhibits excellent overall hydrophilicity. The oxygen-containing functional groups of the carbon nanotubes and the hydrophilic groups of the polyaniline, combined with the capillary channels within the cellulose aerogel, can rapidly and continuously supply moisture to the multi-stage modified photothermal layer. Water droplets are completely absorbed within 0.1 seconds upon contact with the composite material, stably maintaining an evaporation state. The porous hydrophilic water transport layer of the cellulose aerogel continuously conducts salt through porous capillary channels. During long-term treatment of saline seawater, salt is carried by the water flow to the interior or bottom of the aerogel, making it difficult for salt crystals to precipitate on the surface of the multi-stage modified photothermal layer, resulting in stable long-term operation of the equipment. The entire preparation process is mild, using commercial carbon fiber paper and carboxylated multi-walled carbon nanotubes as raw materials. The multi-level modified photothermal layer can be prepared simply by ultrasonic impregnation, electrochemical deposition, and low-temperature in-situ polymerization. No high-temperature sintering or complex equipment is required. The device is bonded and assembled using a mixture of polyvinyl alcohol and cellulose nanoparticles. The finished product has a robust structure, which is convenient for large-scale production and multi-scenario integrated applications.
Claims
1. A composite solar evaporator using CNTs in conjunction with Ni and PANI, characterized in that: The invention comprises a multi-level modified photothermal layer and a porous hydrophilic water-transporting layer. The multi-level modified photothermal layer includes a substrate, the surface of which is sequentially coated from the inside out with a three-dimensional porous network layer of carbon nanotubes, an intermediate metal particle layer, and a conductive polymer layer. The porous hydrophilic water-transporting layer is bonded to the bottom surface of the multi-level modified photothermal layer and has a three-dimensional porous capillary network structure for continuous water supply and resistance to salt crystallization.
2. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 1, characterized in that: The construction sequence of the multi-level modified photothermal layer is as follows: first, a three-dimensional porous carbon nanotube network layer is constructed on the substrate surface; then, an intermediate metal particle layer is constructed on the surface of the three-dimensional porous carbon nanotube network layer; finally, a surface conductive polymer layer is constructed on the surface of the intermediate metal particle layer to obtain the multi-level modified photothermal layer; a porous hydrophilic water-conducting layer is composited on the bottom surface of the multi-level modified photothermal layer to obtain the multi-level modified composite solar evaporator.
3. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 2, characterized in that: First, a three-dimensional porous network layer of carbon nanotubes is constructed on the surface of the substrate, including: The substrate is immersed in a carbon nanotube dispersion for impregnation treatment, so that the carbon nanotubes are loaded on the surface and gaps of the substrate and form a three-dimensional porous network structure, thus obtaining the carbon nanotube three-dimensional porous network layer.
4. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 3, characterized in that: The carbon nanotube dispersion is prepared by dispersing carboxylated multi-walled carbon nanotubes and a carbon nanotube dispersant in deionized water at a mass ratio of 0.8 to 1.2:1; the diameter of the carboxylated multi-walled carbon nanotubes is 10 to 30 μm; the mass fraction of the carbon nanotube dispersion is 0.2 wt% to 1 wt%; the impregnation treatment is ultrasonic impregnation treatment, and the treatment time is 25 to 35 min; the impregnation treatment also includes the steps of washing and drying at 60°C for 1 to 3 h.
5. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 3, characterized in that: The step of further constructing an intermediate metal particle layer on the surface of the three-dimensional porous network layer of carbon nanotubes includes: Metal particles are loaded onto the surface of the three-dimensional porous network layer of carbon nanotubes through a deposition process to increase the surface micro-roughness and provide attachment sites for the surface conductive polymer layer, thereby obtaining the intermediate metal particle layer.
6. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 5, characterized in that: The metal particles are nickel particles; The deposition process is an electrochemical deposition process, which includes: using the substrate loaded with the three-dimensional porous network layer of carbon nanotubes as the cathode and a pure nickel sheet as the anode, performing electrochemical deposition in a nickel sulfate electrolyte at a constant current of 0.8 to 1.2 A for 4 to 6 minutes; The electrochemical deposition process also includes a cleaning step followed by drying at 60°C for 1–3 hours.
7. The method for preparing the composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 5, characterized in that: The final step of constructing a conductive polymer layer on the surface of the intermediate metal particle layer includes: A conductive polymer layer is formed on the surface of the intermediate metal particle layer through a polymerization process to obtain the conductive polymer layer.
8. The method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 7, characterized in that: The conductive polymer layer is a polyaniline layer; The polymerization process is an in-situ oxidative polymerization process, which includes: immersing the substrate loaded with the intermediate metal particle layer in an aniline solution with a concentration of 0.25-0.35 mol / L, then adding an ammonium persulfate solution with a concentration of 0.25-0.35 mol / L, and carrying out the oxidative polymerization reaction at a low temperature of 0-5°C for 3-5 hours; The oxidative polymerization reaction is followed by washing and drying at 60°C for 1–3 hours.
9. The method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 7, characterized in that: The step of assembling a porous hydrophilic water-conducting layer onto the bottom surface of the multi-level modified photothermal layer includes: A cellulose aerogel is bonded to the bottom surface of the multi-stage modified photothermal layer using an adhesive to form the porous hydrophilic water-conducting layer.
10. The method for preparing a composite solar evaporator of CNTs synergistic with Ni and PANI according to claim 9, characterized in that: The cellulose aerogel is prepared by freezing and freeze-drying a mixed solution of polyvinyl alcohol and nanocellulose with liquid nitrogen. The freeze-drying temperature is -55 to -45°C and the vacuum degree is 0.05 to 0.07 MPa. The adhesive is a mixed solution of polyvinyl alcohol and nanocellulose. After bonding, the process also includes a curing step of drying at 60°C for 1 to 3 hours.